HUBUNGAN TEACHER ENGAGEMENT DAN PELATIHAN DENGAN KINERJA GURU TK - Hendariah Hendariah (JTPPm (Jurnal Teknologi Pendidikan dan Pembelajaran) : Edutech and Intructional Research Journal, 2020)
The purpose of this study was to determine the relationship of teacher engagement and training with the performance of Kindergarten Teachers in Teluknaga District, Tangerang Regency. This type of research is a quantitative field research with a correlational approach. This research was conducted at TK se-Kecamatan Teluknaga Tangerang Regency Banten. The population in this study was kindergarten teachers in Teluknaga Subdistrict, Tangerang Banten Regency with a total sample of 50 teachers. The results showed that: 1) The results of the correlation analysis in the first hypothesis test, there is a relationship between teacher engagement with teacher performance, this is  evidenced  by  the  tcount>  ttable  (14.98>  2.011);  2)  the  second  hypothesis  is concluded that there is a relationship between training and the performance of teachers in kindergartens in Teluknaga District, Tangerang Regency, this is evidenced by the value of tcount> ttable (3,961> 2,011); 3) the third hypothesis is the relationship of teacher engagement and training together with the performance of teachers in kindergartens in Teluknaga District, Tangerang Regency. This is evidenced by the value of Fcount> Ftable (26.582> 3.195). The magnitude of the contribution of teacher engagement and school training contributes to teacher performance, judging by the R Square value of 0.843 (84.3%), this means that together teacher engagement and school training contribute 84.3% to the performance of  teachers in kindergarten in Teluknaga Sub-District, Tangerang Banten District, and the remaining 15.7% of the performance of kindergarten teachers in the Teluknaga Sub-District, Tangerang Banten District, was contributed by other factors beyond teacher engagement and school training. Keywords: Teacher Engagement, Training, Teacher Performance